The conflict of power in the Ottoman Empire And his influence on the system of rule from the fourteenth to eighteenth century. - yossef, Elham; hasan, Samee (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The question of the transition of power in the Ottoman Empire, an important issue shed Ottoman sultans, and occupied their mind for long periods, as they interned them in the midst of civil conflicts and local war, have been instrumental and head in a broad and fundamental to the regime and the quality of the ruling lines, as have contributed to the emergence of the forces involved sultans and their influence was able to sneak into the decision-making centers and succeeded later in the appointment of the sultans and withheld from their basic tasks in the leadership of the state and society, paving the way for the conversion of the Ottoman government and the Alslltani Palace to the headquarters of the rival gangs competing. Doing all effort to harness the potential of all state of the army and of the financial treasury to buy military alliance and issue decision reflected negatively on the society in which they toil under a huge financial burden in order to provide the necessary cash-turned collected main recipe for the rulers and leaders. Army no longer provides the honor of the empire and sanctifies the sultan to comply with his orders as spiritual father to them but turned into tools brutalize sultans and take over others, especially that they were only puppets or animated structures for sultans helpless unable to take crucial decision.